Faculty Motivation and Research Productivity in Nepal’s Community Campuses: A Quantitative Analysis - Thapa, Matrika; Karki, Mohan Kumar; Shrestha, Surendra Babu (Academic Journal of Sukuna, 2025)
The level of faculty motivation regarding the publication of research is very important towards expansion of academic knowledge, institutional and professional growth. The study deals with the intrinsic and extrinsic issues that affect the research productivity of the faculty members in the community campuses, and the assistance and challenges of the faculty members in community campus settings. Among the data collected, the quantitative method was used to collect data among faculty members using structured questionnaires. Descriptive statistics (mean and standard deviation), along with inferential statistics (ANOVA, independent t- tests and multiple regression analysis) were used in the examination of the data. The results indicate that intrinsic factors, or those factors related to intellectual satisfaction and personal interest are significant drivers of the productivity of research, whereas the extrinsic factors, or those circumstances associated with career promotion and financial rewards also influence the productivity of research. Nevertheless, it was also determined that institutional support was very poor with the most notable problems being high teaching loads, restrained research resources, and time restraints. There was also evidence regarding gender-based and age gap in research output. In the study, both the issues and the suggested solutions point to the necessity of institutional changes, such as improved levels of funding research, higher levels of mentorship, and workload reduction, to provide a more favorable research environment. These lessons carry useful implications to policymakers, teachers, and administrators at the community campuses who want to enhance academic faculty interested in the publication of research works.